Poetic ethics in Proverbs: wisdom literature and the shaping of the moral self - Stewart, Anne W. (Cambridge University Press, 2016)
The Book of Proverbs' frequent use of binary oppositions - righteous and wicked, wise and foolish - has led many to assume that its vision of the moral world is relatively simplistic. This study demonstrates that Proverbs in fact presents a remarkably sophisticated response to ethical questions of profound concern to the Israelite sages who crafted the book: what motivates human beings? How do they learn? How does the power of desire shape human characters? Anne W. Stewart analyzes Proverbs' multifaceted collection of images and metaphors to reveal their complex understanding of the development of the moral self, which suggests that character formation requires educating all of the senses and not simply the cognitive faculties. One of few works to make explicit connections between the poetic form of Proverbs and its pedagogical function, Poetic Ethics in Proverbs will appeal to all those interested in literary approaches to the Bible.